Dynamic Transcription of Distinct Classes of Endogenous Retroviral Elements Marks Specific Populations of Early Human Embryonic Cells - Göke, Jonathan (2016)
About half of the human genome consists of highly repetitive elements, most of which are considered dispensable for human life. Here, we report that repetitive elements originating from endogenous retroviruses (ERVs) are systematically transcribed during human early embryogenesis in a stage-specific manner. Our analysis highlights that the long terminal repeats (LTRs) of ERVs provide the template for stage-specific transcription initiation, thereby generating hundreds of co-expressed, ERV-derived RNAs. Conversion of human embryonic stem cells (hESCs) to an epiblast-like state activates blastocyst-specific ERV elements, indicating that their activity dynamically reacts to changes in regulatory networks. In addition to initiating stage-specific transcription, many ERV families contain preserved splice sites that join the ERV segment with non-ERV exons in their genomic vicinity. In summary, we find that ERV expression is a hallmark of cellular identity and cell potency that characterizes the cell populations in early human embryos.